Simultaneous changes in serum HMGB1 and IFN-α levels and in LAIR-1 expression on plasmatoid dendritic cells of patients with juvenile SLE.. New therapeutic options?. (March 2014) - Kanakoudi-Tsakalidou, F; Farmaki, E; Tzimouli, V; Taparkou, A; Paterakis, G; Trachana, M; Pratsidou-Gertsi, P; Nalbanti, P; Papachristou, F
We investigated the simultaneous changes in serum levels of HMGB1 and IFN-α as well as in LAIR-1 expression on plasmatoid dendritic cells (pDCs) of juvenile systemic lupus erythematosus (jSLE) patients in order to explore their involvement in the disease pathogenesis and their correlation with disease activity and other characteristics. In total, 62 blood samples were studied from 26 jSLE patients (18 girls), aged 8–16 years. Twenty healthy subjects (16 girls) of comparable age were included as healthy controls (HCs). Concentrations of serum HMGB1 and IFN-α were assessed by ELISA and LAIR-1 expression on pDCs by five-color flow cytometry. The disease activity index was assessed by SLEDAI and ECLAM scores. It was found that mean serum levels both of HMGB1 and IFN-α were significantly increased in jSLE patients compared to HCs and in jSLE patients with active disease with or without active nephritis compared to those with inactive disease. Mean serum levels of HMGB1 were positively correlated with levels of IFN-α and both were positively correlated with the SLEDAI and ECLAM scores. The expression of LAIR -1 on pDCs of jSLE patients was significantly lower than that of HCs. In conclusion, our findings indicate that serum HMGB1 not only represents a potential marker of disease activity but together with the lack of LAIR-1 inhibitory function may contribute to the sustained inflammatory action of IFN-α in jSLE. In this regard, blocking the action of HMGB1 and its receptors or enhancing the expression/inhibitory function of LAIR-1 on pDCs should be included in future immune interventions for controlling jSLE.